ANALISIS EMPAT STANDAR KOMPETENSI GURU DI LINGKUNGAN SEKOLAH DASAR - Kurnia, Ira Restu; Barokah, Awalina; Edora, Edora; Syafitri, Inayah (Jurnal Pendidikan Dasar, 2024)
This research is motivated by awareness of the importance of teacher competence in implementing learning. This research describes the teacher competencies possessed by teachers at SDN Mekar Mukti 05. The research method used is a descriptive qualitative method. Researchers used observation and interview instruments with research subjects. The research results showed that teachers at SDN Mekar Mukti 05 have four competency standards that teachers must have. The activities carried out always reflect efforts to always improve these competencies in order to realize effective learning and achieve learning goals. Keywords: Competence, Teacher, Learning